SEISMIC INVESTIGATIONS ALONG THE WESTERN SECTOR OF ALPHA RIDGE, CENTRAL ARCTIC OCEAN - Jokat W. (My University, 2003)
During the summer of 1998 a two-ship experiment with the Russian nuclear icebreaker Arktika and RV Polarstern probed the central part of Alpha Ridge in the High Arctic. In total 320 km of multichannel seismic data were acquired along three profiles supplemented by four sonobuoys. The sonobuoys provided velocity control for the sedimentary sequences and for the upper crust. The sediment velocities range from 1.6 to 2.7 km s-1 and the sediment thicknesses vary between 500 and 1200 m. The units lie conformably on the basement. Only minor faulting is visible in the area of Lyons Seamount. In general, the sediments can be divided into two units. Their age is quite hypothetical: the upper unit is most probably to be of Cenozoic and the lower of Cretaceous age. The interpretation of the seismic velocities suggests oceanic basement. The basement velocities range from 4.3 to 6.7 km s-1. In combination with a recovered basalt sample there is little doubt of the oceanic origin of Alpha Ridge, at least in its western sector.
Keywords: ALPHA RIDGE; ARCTIC OCEAN; SEISMIC REFLECTION; Cenozoic; Cretaceous; Cenozoic; Кайнозой; Mesozoic::Cretaceous; Мезозой::Меловая